PENGARUH INFLASI, EKSPOR, IMPOR DAN SUKU BUNGA LUAR NEGERI TERHADAP NILAI TUKAR RUPIAH ATAS DOLAR AMERIKA PERIODE JANUARI 2014 S.D. DESEMBER 2018 - HADI PRANOTO; RUSMIN NURYADIN (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Unstable Fluctuation in the rupiah exchange rate against the US dollar can be affected by domestic and global economic conditions, the condition of these macroeconomic factors can make the exchange rate depreciate or appreciate.The model in this study uses a Vector Auto Regression-Vector Error Correction Mode (VAR-VECM) to see the effect of short and long term and the surprise of each variable on the response in the period January 2014 to December 2018.Based on the result of the hypothesis the VAR-VECM model shows in the long run that exports have asignificant and foreign interest rates have a significant and negative effect on the rupiah exchange rate against the dollar. While other variable of inflation do not have a significant and positive effect on the rupiah exchange rate against the dollar. In the short term, only the variable rupiah exchange rate variable against the dollar is significant to itself in the 1st, 3rd, and 5th lags, the import variable in the 3rd lag and the foreign interst variable in the 5th lag. While other variable do not have a significant effect in the short term.Based on the highest Response Impulse analysis, the response of the rupiah exchange rate to the dollar itself shows a postive overall response and will be relatively stable at around 0,12%. The next highest response is that inflation show a positive response and will be relativerly stable at around 0,07%. The export response was relatively stable in the range of 0,10%, but showed a negative response. Then the import respon shows a negative and will be relatively stable at around 0,01%. The last response to foreign interest rates showed a postive response and was relatively stable at around 0,01%.Based on the analysis Variance Decomposition, the biggest contribution to the variable exchange rate of the rupiah against the US dollar is the variance of the rupiah exchange rate against itself, followed by the second  largest contribution, namely inflation, followed by the variance of exports, imports and foreign interest rates respectively. Keywords: inflation, export, import, foreign interest rates, rupiah exchange rate, time series, Vector Autoreggression-Vector Error Correctio  Model (VAR-VECM)